Stereopsis and visual acuity: Bilateral trifocal versus blended extended depth of focus and diffractive bifocal intraocular lenses - Zhu, Meiyi; Fan, Wei; Zhang, Guangbin (Frontiers in Medicine, 2022)
Purpose: To compare stereopsis and visual acuity (VA) between bilateral implantation of trifocal intraocular lenses (IOL) and blended implantation of an extended depth of focus (EDOF) IOL with a bifocal IOL. Methods: This is a non-randomized, prospective comparative study included 74 eyes of 37 patients who underwent phacoemulsification and bilateral implantation of AT LISA tri 839MP IOL (bilateral group; 21 patients) or blended implantation of Tecnis Symfony ZXR00 and Tecnis ZLB00 IOL (blended group; 16 patients). The primary outcomes were stereoacuity and binocular VA. The secondary outcomes were visual defocus curve, quality of life, and patient satisfaction. Follow-up was performed 3 months after the surgery. Results: The mean near stereoacuity was 49.76 ± 22.67 and 120.63 ± 90.94 seconds of arc (arcsec) in the bilateral and blended groups, respectively (P < 0.001). Near stereoacuity was positively correlated with VA difference of two eyes (r = 0.896, P < 0.001). The mean binocular uncorrected visual acuity at 40 cm, 80 cm, 5 m, and corrected distance visual acuity at 5 m of the bilateral and blended groups was not statistically significant different. The bilateral group had better VA at a vergence from −2.5 to −4.0 D. Both groups obtained high quality of life and patient satisfaction scores. Conclusions: The bilateral and blended groups achieved good binocular VA, quality of life, and high patient satisfaction. However, the near stereoacuity of the blended group was worse.